2015
DOI: 10.1055/s-0034-1391230
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic enterography adds value to colonoscopy in differentiating Crohn’s disease from intestinal tuberculosis: a potential diagnostic algorithm

Abstract: CTE adds unique information to colonoscopy in differential diagnosis between Crohn's disease and ITB, allowing correct diagnosis in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 15 publications
3
48
0
2
Order By: Relevance
“…Seven studies reported the median and seven studies reported the mean duration of symptoms. The median duration in CD (6–53.3 months, range 0.3–300 months) was significantly greater than that in ITB (3–23.4 months, range 0–120 months) in five of the studies (1,6,1214,16,30). In the other studies, the reported mean duration of symptoms in meta-analysis was 26.5 months (95% CI=15.7–37.3) longer for CD compared with that for ITB (2,11,15,31–34).…”
Section: Resultsmentioning
confidence: 79%
“…Seven studies reported the median and seven studies reported the mean duration of symptoms. The median duration in CD (6–53.3 months, range 0.3–300 months) was significantly greater than that in ITB (3–23.4 months, range 0–120 months) in five of the studies (1,6,1214,16,30). In the other studies, the reported mean duration of symptoms in meta-analysis was 26.5 months (95% CI=15.7–37.3) longer for CD compared with that for ITB (2,11,15,31–34).…”
Section: Resultsmentioning
confidence: 79%
“…This model had high specificity and positive predictive value; however, the sensitivity was relatively low because of the low frequency of individual features in either disease. Numerous recent studies have also evaluated the role of CT in differentiating between CD and ITB 2021222324. Therefore, we tried to collate the results of all these studies to evaluate the overall role of CT in differentiating between CD and ITB.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, clinical and endoscopic response to therapy for CD was required to confirm the final diagnosis of CD. 12 A total of 16 patients with ITB and 52 patients with CD were selected for this study. Biopsies of all cases were taken before definitive treatment was started.…”
Section: Methodsmentioning
confidence: 99%